The effect of oxytocin and cloprostenol administration via umbilical artery on fetal membrane removal in cows with dystocia - Akar, Y.; Kizil, O.; Saat, N.; Yuksel, M. (Wiley-Blackwell, 2011)
[Abstract Not Available]
15th Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- SEP 15-17, 2011 -- Antalya, TURKEY